Design Considerations for Pumping Stations Using Variable Speed Pumps - Farzin Salmasi; John Abraham; Arian Salmasi (Novel Perspectives of Engineering Research Vol. 10, 2022)
Because of its simplicity, a constant speed pump is frequently employed in pressured water distribution systems. Constant-speed pumps, on the other hand, struggle to cope with fluctuating water flow needs. When the discharge demand differs from the design discharge, the needed demand (discharge and head) can be fulfilled by simply altering the pump speed without making any other system changes. In this study, the efficiency of stations equipped with variable speed pumps under all operating conditions exceeds that of stations equipped with fixed speed pumps. The use of variable speed pumps not only increases efficiency but also aids in meeting water needs. In this study, the application of variable speed pumps in pressurized irrigation systems is investigated. The chosen pump station contains an actual sprinkler irrigation system with three lateral lines and a 600-meter main pipe near Tabriz, Iran. The primary pipes are 8 and 6 inches in diameter. The use of a variable speed pump enhances average pump efficiency by 18.7%, according to the findings. In addition, as compared to a fixed speed pump, the variable speed pump system saves 57.6% on electricity. As a result, variable speed pumps should be used in pressurised systems. This research contributes step-by-step calculations for sprinkler irrigation system design. Engineers who are unfamiliar with the commutation procedure will benefit from this knowledge.